6x+22x-5=7(4x+9)

Simple and best practice solution for 6x+22x-5=7(4x+9) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6x+22x-5=7(4x+9) equation:



6x+22x-5=7(4x+9)
We move all terms to the left:
6x+22x-5-(7(4x+9))=0
We add all the numbers together, and all the variables
28x-(7(4x+9))-5=0
We calculate terms in parentheses: -(7(4x+9)), so:
7(4x+9)
We multiply parentheses
28x+63
Back to the equation:
-(28x+63)
We get rid of parentheses
28x-28x-63-5=0
We add all the numbers together, and all the variables
-68!=0
There is no solution for this equation

See similar equations:

| 15q−-19q+-7q+-12q+4q=19 | | 4y-4+24=360 | | 10x+15+135=360 | | -28=5(v-3)+8v | | 7x+21x-2=7(4x+1) | | -6+15=2x+9 | | −4(−3x−2)+4x+5=  −3−3 | | 4y-4+24=180 | | 3t-48=27 | | 101.6=3.2(7.5x+7) | | -3(y+3)=4y-1+2(4y+5) | | 3x-4=110 | | 4w+3(1+2w)=23 | | 99=-4(5x+4)-5 | | 4g+31=283 | | -3x+36=x=16 | | -4(1-5x)=-124 | | 4(u-6)-8u=4 | | -4(1-5k)=-124 | | 4.1(6+7.4x)-6.4x=144.3 | | 8x+52=8x+6 | | 3=r8− 3 | | 8−2h=2 | | 7=f2+4 | | -3(-2u+7)-9u=3(u-1)-9 | | 7=f2+ 4 | | 292=98-x | | 6=6u+2(u-7) | | 89.64=3(7.2+5.4p) | | 53*x=424 | | 0.12x=19200 | | 89.64=3(7.2+5.4x) |

Equations solver categories